France in an age of globalization - Védrine, Hubert 1947- (Brookings Institution Press, 2001)
"This book takes the form of a dialogue between French foreign minister Hubert Vedrine and international relations expert Dominique Moisi. In this conversation, Vedrine spells out his vision of the U.S. "hyperpower," France's role in the world, Europe's future, the current structure of the international system, and the role of ethics in international affairs." "An earlier, French-language version of this work was published under the title Les cartes de la France a l'heure de la mondialisation (France's Assets in an Age of Globalization) in spring 2000. This English-language version adds extensive new material and covers many important developments, including Vedrine's assessments of the 2000 U.S. presidential election; the July-December 2000 French presidency of the European Union; the breakdown of the Middle East peace process; and developments in Russia, Africa, and Asia."--BOOK JACKET.
Includes index
Keywords: Védrine, Hubert; Moïsi, Dominique; Védrine, Hubert -- 1947-; World politics / 1995-2005; Globalization; Politique mondiale / 1995-2005; Mondialisation; Mondialisation / France; Buitenlandse politiek; Franstaligheid; Amerikanisatie; Internationalisatie; Außenpolitik; Globalisierung; Politik; France / Foreign relations / 1981-; France / Foreign relations / United States; United States / Foreign relations / France; United States / Foreign relations / 1993-2001; France / Relations extérieures / 1981-; France / Relations extérieures / États-Unis; États-Unis / Relations extérieures / France; États-Unis / Relations extérieures / 1993-2001; Francia / Relaciones exteriores / 1981-; Francia / Relaciones exteriores / Estados Unidos; Estados Unidos / Relaciones exteriores / Francia; Estados Unidos / Relaciones exteriores / 1993-2001; Frankreich; USA; Interview